THE IMPACT OF RACIAL DISCRIMINATION TOWARDS SOCIAL LIFE IN THE NOVEL THE DIARY OF A YOUNG GIRL BY ANNE FRANK - Agil Setyanto; Janah, Ulum (Prologue: Journal on Language and Literature, 2024)
This thesis studies the impact of racial discrimination on social life in the novel The Diary of a Young Girl by Anne Frank. There are two research objectives for this research: 1) To find the forms of racial discrimination in the novel The Diary of a Young Girl by Anne Frank, and 2) To describe the impact of racial discrimination on social life in the novel. The theory used in this research is Racial Discrimination by Rosita Fibbi et al. The methodology employed is qualitative research, in which the researcher presents the issues descriptively. The researcher collected the data from The Diary of a Young Girl, which serves as the primary data for this research, and the researcher analyzed and interpreted the data from the quotation in the novel. After going through the study, the researcher found two forms of racial discrimination by the Germans against Jews, namely direct discrimination and indirect discrimination. Furthermore, the racial discrimination by the Germans against the Jews impacts their social lives. The impacts to Anne's family and relatives, and all the Jews social life, such as the impact on their economy, their social chances, and their psychological.